Democratic Leadership Profile of The Principal in Improving Interpersonal Relations of Teachers at SMP Negeri 3 Welahan - Fauzi, Noor Ali; Bunyamin; Murniati, Ngurah Ayu Nyoman (Graduate Program Magister Manajemen Pendidikan, 2025)
This qualitative case study research examines the implementation of democratic leadership by the principal in improving interpersonal relationships at SMP Negeri 3 Welahan. Data were collected through interviews, observations, and documentation studies with the principal and five teachers as key informants. The principal developed an open, effective, and inclusive communication pattern, characterized by constructive two-way communication. The strategies implemented include regular meetings, group discussions, utilization of digital platforms, and communication skills training for teachers. The principal also understands teachers' obstacles through an empathetic approach and direct communication, using observations, personal interviews, and periodic surveys, then follows up with special assistance or training. In maintaining group cooperation, the principal carries out collaborative coaching through the development of a school community of practitioners with a teamwork pattern, as well as strengthening communication skills. This coaching pattern includes structured discussions, peer guidance, and collaborative activities. The principal provides systematic feedback on the analysis of the needs of the school community of practitioners through direct discussions and written documents, usually during evaluations or regular discussion forums. The recommendation of this study is to develop an inclusive participatory decision-making strategy by facilitating effective and empathetic collaboration and interaction.